Comparative Analysis of Erythrocyte Proteomes of Water Buffalo, Dairy Cattle, and Beef Cattle by Shotgun LC-MS/MS - Guo, Jiaying; Sun, Yali; Tian, Yu; Zhao, Junlong (Frontiers in Veterinary Science, 2019)
A number of studies have demonstrated that Babesia orientalis (B. orientalis) can only infect water buffalo (Bubalus bubalis) and not dairy cattle (Bos taurus) or beef cattle (Bos taurus), even though all three belong to the tribe Bovini and have close evolutionary relationships. In addition, Babesia species are intracellular protozoans that obligately parasitize in erythrocytes. This may indicate that the infection specificity is due to differences in erythrocyte proteins. Totals of 491, 1,143, and 1,145 proteins were identified from water buffalo, beef cattle, and dairy cattle, respectively, by searching the Uniprot and NCBI databases. The number of proteins identified for water buffalo was far lower than for beef cattle and dairy cattle, particularly in the range from 15 to 25 kDa. Remarkably, 290 identified proteins were unique to water buffalo, of which putative gamma-globin and putative epsilon-globin had a significant possibility of being relevant to the survival of B. orientalis only in water buffalo. A total of 2,222 proteins were annotated in terms of molecular function, biological process, and cellular component according to GO annotation. The number of proteins of water buffalo in oxygen binding was far higher than for beef cattle and dairy cattle. This is the first time that the protein profiles of water buffalo, beef cattle, and dairy cattle have been comparatively analyzed. The uniquely expressed proteins in water buffalo obtained in this study may provide new insights into the mechanism of B. orientalis infection exclusivity in water buffalo and may be a benefit for the development of strategies against B. orientalis.